Tracheal Intubation with Aura-i and aScope-2: How to Minimize Apnea Time in an Unpredicted Difficult Airway - Vittorio Pavoni; Valentina Froio; Alessandra Nella; Martina Simonelli; Lara Gianesello; Andrew Horton; Luca Malino; Massimo Micaglio (Case Reports in Anesthesiology)
The supraglottic airway’s usefulness as a dedicated airway is the subject of continuing development. We report the case of an obese patient with unpredicted difficult airway management in which a new “continuous ventilation technique” was used with the Aura-i laryngeal mask and the aScope-2 devices. The aScope-2/Aura-i system implemented airway devices for the management of predictable/unpredictable difficult airway. The original technique required the disconnection of the mount catheter from Aura-i, the introduction of the aScope-2 into the laryngeal mask used as a conduit for video assisted intubation and then towards the trachea, followed by a railroading of the tracheal tube over the aScope-2. This variation in the technique guarantees mechanical ventilation during the entire procedure and could prevent the risk of hypoventilation and/or hypoxia.